Impact of External Environmental Factors and Financial Instruments on Development of Innovations and Ecotourism in Construction Sector of Mountain Regions - Soltogulova, Mirgul; Abdraimova, Baktygul; Namazalieva, Meerim; Alieva, Nasikat; Abdralieva, Gulzaada (Journal of Environmental Accounting and Management, 2026)
The purpose of this study was to analyse the impact of external environmental factors and financial instruments on the development of sustainable ecotourism in mountain regions. The methodology included surveys and correlation analysis, with the primary focus on analysing external factors and financial instruments applied in mountain regions. The survey revealed differences in perceptions of support between local residents and entrepreneurs, particularly in terms of the availability of financial resources and participation in ecotourism initiatives. The correlation analysis confirmed that a high level of investment in ecotourism was associated with positive evaluations of its development. Specifically, among respondents who indicated high investment levels, 70% rated the development as "high" or "very high". In contrast, among those who reported low investment levels, positive ratings did not exceed 30%. These findings highlight the importance of creating a favourable investment environment. Additionally, the analysis of external factors, including natural and climatic limitations, transport accessibility, and administrative barriers, revealed their impact on the implementation of ecotourism projects in mountain regions. The study also identified the most effective financial instruments, such as public-private partnerships, grant support, and mixed financing models. The practical significance of the results lies in their potential use for developing support programs for ecotourism in mountain regions, including the creation of financial mechanisms aimed at stimulating investments, as well as providing recommendations for government bodies and local communities to enhance the effectiveness of implemented initiatives.